ANALISIS PENGENDALIAN PROSES SUPPLY CHAIN MANAGEMENT PRODUKSI TAHU NR KARAWANG - Rizka Adinda Nurkhoridah; Tiawan; Vivi Ayu Lestari; Lila Setiyani; J Rolles Herwin Sihombing; Amanda Agustina; Asep Obay Badillah; Mutia Nur Anisya; Riaz Citra Hardiman (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
This research analyzes the SCM (Supply Chain Management) process control in NR tofu production in Karawang. Observational and interview methods are used to collect data about production processes and supply chain management. The results show the need to improve information system integration, coordination between production units, and monitoring of raw material quality. Implementation of new technology and employee training were identified as potential solutions. This research provides insights for NR tofu producers to improve the efficiency and efficiency of their supply chains, contributing to quality and competitive advantage.